Scientific and practical prerequisites for the formation of educational activities of preschool children in multilevel education - Abdykadyrov, Askhat (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the problems of continuity and continuity of preschool education, scientific and practical prerequisites, in the transition to multilevel education. Analyzed new methods and techniques that provide continuous communication when moving to a new level of education. Identified problems and errors at all stages of multilevel education. Achieving a holistic system of transition between the levels of education, the formation of an educational path, the definition of the principles of lifelong education, in interconnection, the learning environment, on the way to quality education.The main idea is to determine effective methods in organizing an educational subject-spatial environment that meets modern requirements, taking into account current problems and gaps in the education of a future student, the search for pedagogically appropriate systems and technologies that ensure the progressive development of the child, his readiness for transition to school - assuming the role active subject of their own educational activities.The need to rethink and rethink pedagogical educational processes and systems, the formation of scientific and practical prerequisites, adaptation in the process of educational activity, in the transition to multi-level education.The goal is to contribute to the formation of educational activities, high-quality preparation for school, to instill the skills of independence and creativity in solving complex problems. Provide motivation for learning, systematize and optimize learning activities, develop analytical activities. The dynamics of the results of the educational activities of preschoolers in multilevel education, when moving to the next level, shows the inadequacy of the formation of the necessary prerequisites for educational activities.The trend of continuity in multilevel education is relevant. It is important to achieve a high level of development of the child, which makes it possible to easily adapt to a new situation, master knowledge, norms of rules of behavior, predicts a high degree of school success. I study the effectiveness of the applied innovative methods on the social and personal development of the child, on the formation of skills for successful learning in elementary school, and the readiness of the pupil to school. I am experimenting with the role of elements of local folklore in musical studies, in the formation of a person’s national identity in interacting with approved methods.Preschool institutions work in conjunction with innovative projects that provide conditions for preparing for school, the prerequisites for educational activities are formed. Preschool education does not provide basic knowledge; children acquire knowledge in different fields of knowledge, interacting with activity in action, as a subject. The child achieves results, forming the prerequisites for educational activities that allow you to master school knowledge. Joint activities in various aspects, the integration of activities, non-traditional forms of training, provides high-quality assimilation of knowledge and skills, a successful result.Thus, the primary tasks of preschool education include the development of: emotional-volitional and cognitive spheres, mental functions, communication skills, and the ability to act according to the rules.The implementation of these tasks allows us to ensure the mental and physical development of children at the level that is necessary for their inclusion in educational activities. Thus, the goal of preparing children for school is not so much mastering specific knowledge as creating prerequisites for schooling.The reasons for the continuity between preschool and school education are: development of the child’s potential capabilities, ensuring a gradual transition from immediacy to arbitrariness, taking into account the “zone of proximal development”, creating conditions for the child to be included in social forms of communication.,